Embedded autonomy : states and industrial transformation - Evans, Peter B., 1944- (Princeton paperbacks., 1995)
In recent years, debate on the state's economic role has too often devolved into diatribes against intervention. Peter Evans questions such simplistic views, offering a new vision of why state involvement works in some cases and produces disasters in others. To illustrate, he looks at how state agencies, local entrepreneurs, and transnational corporations shaped the emergence of computer industries in Brazil, India, and Korea during the seventies and eighties.